Innovative Mentorship Program Equips English-Speaking Quebecers With Workplace French Skills - Provincial Employment Roundtable (PERT) (2024)

Un programme novateur de mentorat pour renforcer les compétences en français des Québécois d'expression anglaise en milieu de travail - Provincial Employment Roundtable (PERT) (2024)

PERT’s Recommendations Included in New Report on the Economic Development of Offi cial Language Minority Communities - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Parcours d'apprenants en langues dans l'écosystème de la formation en français au Québec - Provincial Employment Roundtable (PERT) (2024)

User Journeys of Language Learners Navigating Québec's French Language Training System - Provincial Employment Roundtable (PERT) (2024)
In recent years, the Québec government has significantly invested in French language training programs to promote greater usage of French in workplaces, schools, and society. Alongside these efforts, public discourse has emerged about the perceptions French-speaking Quebecers hold of English speakers, many of whom believe that English speakers are not committed to learning or using French despite the availability of publicly funded French language training resources. To explore these issues, this study examines the experiences, motivations, and barriers faced by English-speaking individuals in the labour force regarding French language training, particularly following the introduction of new services by Francisation Québec in June 2023. In doing so, we develop a broad typology of different language learners and explore their language-learning journey through interviews regarding their experiences and perceptions of the French language, language training, and navigating Québec’s labour market. We also interview subject matter experts to identify types of language learners and key themes. We then discuss the impact that these different experiences have on language learners’ outcomes, as well as the types of policy and program approaches that could improve their experiences with adult French language training programs.

Appel à une action concertée pour lever les obstacles à l’emploi des Québécois d’expression dans la Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)

New Report Calls for Coordinated Action to Tackle Employment Barriers Facing English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)

English Speakers in Gaspésie–Îles-de-la-Madeleine Experience the Highest Unemployment Rate in Québec, New Report Finds - Provincial Employment Roundtable (PERT) (2024)

Les Québécois d’expression anglaise de la Gaspésie-Îles-de-la-Madeleine connaissent le taux de chômage le plus élevé au Québec, selon un nouveau rapport - Provincial Employment Roundtable (PERT) (2024)

English Speakers in the Laurentides Face Growing Economic Challenges, New Report Shows - Provincial Employment Roundtable (PERT) (2024)

Les Québécois d’expression anglaise des Laurentides sont confrontés à des défis économiques croissants, selon un nouveau rapport - Provincial Employment Roundtable (PERT) (2024)

English Speakers in Montérégie Facing Increased Unemployment and Ongoing Economic Disparities as Compared to Francophones - Provincial Employment Roundtable (PERT) (2024)

Les Québécois d’expression anglaise de la Montérégie font face à un taux de chômage accru et à des disparités économiques persistantes par rapport aux francophones - Provincial Employment Roundtable (PERT) (2024)

Participation à la conférence de l’ACFAS sur les femmes officielles des communautés linguistiques minoritaires à Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Les nouvelles données du recensement pour la région de la Côte-Nord n'indiquent aucune amélioration de la vitalité économique des Québécois d’expression anglaise depuis 2016 - Provincial Employment Roundtable (PERT) (2024)

New Census Data for Côte-Nord Shows No Improvement in the Economic Vitality of English Speakers Since 2016 - Provincial Employment Roundtable (PERT) (2024)

Attending the ACFAS Official Women Minority Language Communities Conference in Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Annual Report 2023-2024 - Provincial Employment Roundtable (PERT) (2024)

Pre-Budget Submission 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
The Provincial Employment Roundtable Table (PERT) is pleased to submit this brief and proposition to the Ministry of Finance’s 2024-25 Pre-budget consultations. Founded in 2020, PERT is a non-profit organization focused on addressing the employment and employability issues that are being faced by Québec’s English-speaking communities. Since its creation, PERT has become the leading voice on the solutions to English speakers’ employment challenges. Through its research and stakeholder coordination work, PERT has published over 25 reports that capture the employment issues and needs of English speakers across all 17 regions of the province and has established a membership of 90 employment service deliverers, educational institutions, regional organizations, and employers. The employment situation of Québec’s English-speaking population continues to worsen, as demonstrated by the higher unemployment rates and French-language barriers that English speakers face in Québec’s labour market. In this brief, we identify two key contributors to the continued employment challenges of English speakers: a lack of targeted employment services and programs for English speakers and a lack of work-integrated French language training programs to help them enter and remain in the labour market. English speakers’ employment and economic challenges are part of the larger economic headwinds that are facing Québec, which include unprecedented labour shortages, demographic decline, and problems with attracting and retaining talent. This mémoire summarizes PERT’s research findings, particularly the employment challenges facing the English-speaking community in Québec, and advances recommendations for the next budget that will address these challenges and help create a more productive, inclusive, and prosperous Québec for all.

Propositions prébudgétaire 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
La Table ronde provinciale de l'emploi (PERT) a le plaisir de soumettre ce mémoire et proposition aux consultations prébudgétaires 2024-25 du ministère des Finances. Fondée en 2020, PERT est une organisation à but non lucratif qui se consacre aux problèmes d'emploi et d'employabilité auxquels sont confrontées les communautés d’expression anglaise du Québec. Depuis sa création, PERT est devenu le principal porte-parole des solutions aux problèmes d'emploi des Québécois d’expression anglaise. Grâce à son travail de recherche et de coordination des parties prenantes, PERT a publié plus de 25 rapports qui décrivent les problèmes et les besoins des Québécois d’expression anglaise en matière d'emploi dans les 17 régions de la province. PERT compte parmi ses plus de 90 membres des prestataires de services d'emploi, des établissements d'enseignement, et des organisations régionales et employeurs. La situation d'emploi de la population d’expression anglaise du Québec continue de se détériorer, comme en témoignent les taux de chômage plus élevés et les obstacles liés à la langue française auxquels les Québécois d’expression anglaise sont confrontés sur le marché du travail québécois. Dans ce mémoire, nous identifions deux facteurs clés qui contribuent aux défis continus des Québécois d’expression anglaise en matière d'emploi : le manque de services et de programmes d'emploi ciblés pour les Québécois d’expression anglaise et le manque de programmes de formation en français intégrés au travail pour les aider à entrer sur le marché du travail et à y rester. Les difficultés économiques et d'emploi des Québécois d’expression anglaise s'inscrivent dans le contexte plus large des vents contraires auxquels le Québec est confronté, notamment les pénuries de main-d'oeuvre sans précédent, le déclin démographique et les problèmes liés à l'attraction et à la rétention des talents. Ce mémoire résume les résultats de la recherche de PERT, en particulier les défis en matière d'emploi auxquels est confrontée la communauté d’expression anglaise du Québec, et propose des recommandations pour le prochain budget qui permettront de relever ces défis et de créer un Québec plus productif, plus inclusif et plus prospère pour tous.